APC-Targeted DNA Vaccination Against Reticulocyte-Binding Protein Homolog 5 Induces Plasmodium falciparum-Specific Neutralizing Antibodies and T Cell Responses - Bjerkan, Louise; Visweswaran, Ganesh Ram R.; Gudjonsson, Arnar; Labbé, Geneviève M.; Quinkert, Doris; Pattinson, David J.; Spång, Heidi C. L.; Draper, Simon J.; Bogen, Bjarne; Braathen, Ranveig (Frontiers in Immunology, 2021)
Targeted delivery of antigen to antigen presenting cells (APCs) is an efficient way to induce robust antigen-specific immune responses. Here, we present a novel DNA vaccine that targets the Plasmodium falciparum reticulocyte-binding protein homolog 5 (PfRH5), a leading blood-stage antigen of the human malaria pathogen, to APCs. The vaccine is designed as bivalent homodimers where each chain is composed of an amino-terminal single chain fragment variable (scFv) targeting unit specific for major histocompatibility complex class II (MHCII) expressed on APCs, and a carboxyl-terminal antigenic unit genetically linked by the dimerization unit. This vaccine format, named “Vaccibody”, has previously been successfully applied for antigens from other infectious diseases including influenza and HIV, as well as for tumor antigens. Recently, the crystal structure and key functional antibody epitopes for the truncated version of PfRH5 (PfRH5ΔNL) were characterized, suggesting PfRH5ΔNL to be a promising candidate for next-generation PfRH5 vaccine design. In this study, we explored the APC-targeting strategy for a PfRH5ΔNL-containing DNA vaccine. BALB/c mice immunized with the targeted vaccine induced higher PfRH5-specific IgG1 antibody responses than those vaccinated with a non-targeted vaccine or antigen alone. The APC-targeted vaccine also efficiently induced rapid IFN-γ and IL-4 T cell responses. Furthermore, the vaccine-induced PfRH5-specific IgG showed inhibition of growth of the P. falciparum 3D7 clone parasite in vitro. Finally, sera obtained after vaccination with this targeted vaccine competed for the same epitopes as PfRH5-specific mAbs from vaccinated humans. Robust humoral responses were also induced by a similar P. vivax Duffy-binding protein (PvDBP)-containing targeted DNA vaccine. Our data highlight a novel targeted vaccine platform for the development of vaccines against blood-stage malaria.